An Approach to Build the Ergonomics of Interactive Software based on MDE - Noulamo, Thierry; Talla, Bernard Fotsing; Lienou, Jean Pierre; Djimeli-Tsajio, Alain (International Journal of Computer Sciences and Engineering, 2023)
The design and implementation of interactive systems and Human-Machine Interfaces (HMI) use different techniques from both software engineering and ergonomics. To improve the productivity and quality of software, automating the development process is an important factor. User interfaces are nonfunctional but complex software components that play a vital role in the development of interactive applications. We propose in this paper an approach for the automatic production of Human-Machine Interfaces (HMI) for the development of interactive applications according to the Model-Driven Engineering (MDE) approach. A source Meta-Model called "DD_IHM" ("Description Diagram for Human-Machine Interfaces"), a target Meta-Model specific to the PHP language called "CGFP" (Context Grammar for PEAR) for the construction of HMIs and, a set of generic rules for transforming a model conforms to the source meta-Model into a model conforms to the target Meta-Model, written in the QVT language are develop. We apply this approach to the creation of a simple online registration platform.